Measurement of the return on investment in education and in-house training - Dziechciarz, Józef (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The level of awareness and acceptance of the need to enhance volume and intensity of investment in education and in-house training is increasing. This phenomenon stems from the following facts: the aging of the European societies; an intense technological and organizational progress; and a noticeable process of extension of the scope and length of professional and personal development and activity; accompanied with employees' expectations for better quality of life. The increase in the level of acceptance of the need for increased investment in education and training of employees is accompanied by new challenges, including, in the first place, the need to redefine the approach to investment in training and to the evaluation of its results. The „High-Efficiency‟ point of view, alongside the assessment of the advisability of investment in education and training within a company, raises the need to move away from the traditional system of input oriented financing (i.e. financing resources) and to move towards output oriented funding (i.e. financing results). In other words, instead of paying for teaching, companies want to pay for teaching results. This means that the companies which finance education and training, rise - in the process of assessing the training results – fundamental questions about the improvement of the efficiency of the company; and how an increase in the qualifications of workers facilitates the achievement of organizational objectives. On the other hand, the training results assessment from the participant‟s point of view includes a question about the efficiency of the supplier of educational and training programs, and whether the supplier is able to achieve the promised results. The existing business reality is that the efficiency and effectiveness assessments often do not go beyond the survey measuring the level of satisfaction and self-esteem of the participants. This, in turn, causes a visible quantitative pressures, accompanied by insufficient care for quality and inability to use modern techniques to measure the impact of education and training on business performance. As a result, many entrepreneurs treat the investment in training and education of their employees solely as an expense and a disruption of operations. This is due to the fact that managers do not see a direct effect of the investments on the performance of the company. In addition, managers fear possible hazards in the form of expense claims; loss of trained personel to competitors‟ companies, or excessive self-empowerment of the employee. The study is devoted to presentation and discussion of modern techniques measuring the effectiveness of investment in education and training. The list of methods includes an analysis based on objectives, the targeted evaluation, systemic evaluation, judicial evaluation, and assessment prior to the program.